The Legal Strength of the Deed of Power to Sell as the Basis for Transfer of Land Rights - Taufik Hidayat Lubis; Rahmat Ramadhani (International Journal Reglement & Society (IJRS), 2021)
In practice, the granting of a power of attorney to sell as above has caused the power to sell to be used as the basis for the process of making an AJB behind the name and at the same time being used as a registration tool for the transfer of land rights at the Land Office where the land is located. Meanwhile, the power of attorney to sell is accompanied by a statement from a notary that explains that the deed of power of attorney to sell is not an absolute power of attorney prohibited by law or that land and buildings as objects in the deed of power of attorney to sell have been paid in full. The procedure used to collect data in this study is in the form of documentation, namely the guidelines used in the form of notes or quotes, searching for legal literature, books and others related to the identification of problems in this study both offline and online. Analysis of legal materials is carried out using the content analysis method which is carried out by describing the material of legal events or legal products in detail in order to facilitate interpretation in the discussion. The granting of power of attorney is specifically regulated in Chapter XVI, book III of the Civil Code where Article 1792 states: